P73 'The mind bubble'- a patient empowerment tool. (18th November 2019) - Parker, K; Smyth, J; Shah, S; Millar, S
Abstract : Aims: Empower our young people and encourage self-management and advocacy -that remains the overarching principle at our diabetes clinic. A key component of this is to understand the expectations of young people and answer questions they seek answers to. By using their checklist and not our own, we may cover fewer items but are more likely to have a purposeful and eventually fruitful conversation. Our aim was to identify each patient' individual goals and tailor discussions accordingly. Methods: We distributed questionnaires, in the form of a 'mind bubble', to young people over 12 years attending paediatric diabetes clinics in our hospital over a two-month period. A 'mind bubble' is a simplified visual questionnaire designed to be user-friendly and engage with young people. Young people were asked 'What would you like to discuss today at your diabetes clinic?' and their responses were then addressed at that attendance. Results: We received 32 completed 'mind bubbles'. The most common response was for advice on hyperglycemia and hypoglycaemia management (44%). 7 responses (22%) were regarding practical advice on holidays and exercise, 6 responses (19%) for specific questions regarding insulin pumps and infusion sets, and 3 (9%) regarding the use of associated computer programmes. 3 responses (9%) asked for education on ketones. Feedback from these were very positive specially from parents who felt their young person was empowered to articulate exactly what they wanted from us. Conclusions: The 'mind bubble' provides a practical way for young people to inform the diabetes team of their expectations for each clinic visit. The wide variety of responses highlights the challenges of engaging with young people with complex, life long conditions, and the need for patient centred care to enable our young people grow in confidence.